Hierarchical SnS2/SnO2 nanoheterojunctions with increased active-sites and charge transfer for ultrasensitive NO2 detection. Issue 15 (6th April 2018) - Hao, Juanyuan; Zhang, Dan; Sun, Quan; Zheng, Shengliang; Sun, Jianyong; Wang, You
Abstract : An ultrasensitive NO2 sensing material was fabricated using ultrafine SnO2 nanoparticle-modified hierarchical SnS2 nanoflowers. Abstract : SnS2 nanosheets with unique properties are excellent candidate materials for fabricating high-performance NO2 gas sensors. However, serious restacking and aggregation during sensor fabrication have greatly impacted the sensing response. In this study, flower-like hierarchical SnS2 was prepared by a simple microwave method and partially thermally oxidized to form hierarchical SnS2 /SnO2 nanocomposites to further improve the sensing performance at low operating temperature. The fabricated SnS2 /SnO2 sensor exhibited ultrahigh response (resistance ratio = 51.1) toward 1 ppm NO2 at 100 °C, roughly 10.2 times higher than that of pure SnS2 nanoflowers. The excellent and enhanced NO2 sensing performances of hierarchical SnS2 /SnO2 nanocomposites were attributed to the novel hierarchical structure of SnS2 and the nanoheterojunction between SnS2 and the ultrafine SnO2 nanoparticles. The SnS2 /SnO2 sensors also exhibited excellent selectivity and reliable repeatability. The simple fabrication of high performance sensing materials may facilitate the large-scale production of NO2 gas sensors.